Determination of four organic acids in sauce-flavor Baijiu by HPLC - YI Zhongwei, CAI Wenchao, YU Peirong, CHEN Wei, SHAN Chunhui, WANG Yurong, QU Dingwu (Zhongguo niangzao)
This study established a method for determining the contents of four organic acids (lactic acid, acetic acid, butyric acid and caproic acid) in sauce-flavor (Jiangxiangxing) Baijiu by HPLC. An InertSustainSwift C18 chromatographic column (4.6 mm×250 mm, 5 μm) was selected. The mobile phase gradient elution was carried out with methanol-0.02 mol/L potassium dihydrogen phosphate aqueous solution (pH=2.30) at a flow rate of 1.0 ml/min, the column temperature was 35 ℃. The quantitative analysis was performed using external standard method. The results showed that all the four organic acids reached baseline separation within 20 min. The method has a good linear relationship (R2>0.997 9) for the determination of lactic acid and acetic acid, butyric acid and hexanoic acid in the mass concentration ranges of 300-4 200 mg/L and 20-400 mg/L, respectively. The detection limits of the four organic acids were 0.003 1-0.005 3 mg/ml, and the quantification limits were 0.009 3-0.016 5 mg/ml. The relative standard deviations of the precision experiments results were below 2%, and the average recovery rates were 95.48%-100.53%. The method was simple to operate, had high precision, and could accurately detect the contents of organic acids in different samples of Baijiu. It was suitable for the determination of four organic acids in Baijiu during production.